Genomic epidemiology of Escherichia coli: antimicrobial resistance through a One Health lens in sympatric humans, livestock and peri-domestic wildlife in Nairobi, Kenya - Muloi, Dishon M.; Hassell, James M.; Wee, B.A.; Ward, M.J.; Bettridge, Judy M.; Kivali, Velma; Kiyong'a, Alice; Ndinda, Christine; Gitahi, N.; Ouko, T.T.; Imboma, Titus; Akoko, James M.; et al. (Springer, 2022)
Background Livestock systems have been proposed as a reservoir for antimicrobial-resistant (AMR) bacteria and AMR genetic determinants that may infect or colonise humans, yet quantitative evidence regarding their epidemiological role remains lacking. Here, we used a combination of genomics, epidemiology and ecology to investigate patterns of AMR gene carriage in Escherichia coli, regarded as a sentinel organism.